2021
DOI: 10.1159/000512738
|View full text |Cite
|
Sign up to set email alerts
|

Uveal Melanoma in Asians: A Review

Abstract: Despite limited data, some differences in the clinical profile can be observed in Asian population when compared with presentation of uveal melanoma (UM) in white population. The incidence of UM is higher in Whites than in Asians. For the purpose of comparison with Asian population, data from North America, Europe, and Australia were considered as that of “white” population. The annual incidence of UM has been reported to be 5–6 cases/million in whites. The incidence in different parts of Asia is estimated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 42 publications
4
36
1
1
Order By: Relevance
“…Choroidal melanoma is the most common primary intraocular malignancy emanating from choroidal melanocytes. The incidence is approximately 5-6 new cases per million per year, depending on ethnicity and age, with a median age of 55 years [ 46 , 47 , 48 ]. Metastases most often affect the liver, followed by the lungs, bone, and skin.…”
Section: Choroidal Melanomamentioning
confidence: 99%
“…Choroidal melanoma is the most common primary intraocular malignancy emanating from choroidal melanocytes. The incidence is approximately 5-6 new cases per million per year, depending on ethnicity and age, with a median age of 55 years [ 46 , 47 , 48 ]. Metastases most often affect the liver, followed by the lungs, bone, and skin.…”
Section: Choroidal Melanomamentioning
confidence: 99%
“…Uveal melanoma (UM) is the most common primary intraocular malignant tumor in adults [ 1 ]. There is a known racial predilection, with higher incidence in Caucasians (5–6 per million) than Asians (0.4–0.6 per million) and Africans (0.3 per million) [ 2 , 3 , 4 ]. Previous studies have demonstrated variable clinical characteristics and outcomes of UM among different ethnicities [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that monosomy 3, as a poor prognostic factor, has a low incidence rate (8%) in enucleated eyes with choroidal melanoma in Iranian patients [ 40 ]. Interestingly it has been reported that the rate of metastasis is lower in the Asian population [ 41 ], especially in middle eastern countries such as Saudi Arabia (metastasis rate of 5%) [ 42 ] and Jordan (metastasis rate of 13%) [ 43 ], which might signify the role of ethnicity in survival from uveal melanoma. In addition, excluding large UM tumors that were candidates for primary enucleation probably affected the rate of metastasis.…”
Section: Discussionmentioning
confidence: 99%